Experimental Investigation on the Performance of Evaporator/Condenser in a Heat Pump Air Conditioner for Electric Vehicles - Dong Junqi; Zhang Guanghua; Tang Qinyuan; Li Yongping; Huang Ningjie (Zhileng xuebao)
The efficiency of an electric vehicle heat pump system has a great influence on the vehicle mileage. In this work, two evaporators/condensers of different configurations were designed forelectric vehicle heat pump system. The effects of experimental conditions and the position of refrigerant inlet and outlet were experimentally investigated. The heating performances of the heat pump air conditioner system under different conditions were explored as well. The experimental results show that there was little discrepancy in the condenser performance between those of a horizontal structure andvertical structure, but when the evaporator/condenser was under an evaporator mode, the performance of the horizontal structure wasimproved by 20% compared to that of the vertical structure. Moreover, the evaporator performance was improved when the inlet of the refrigerant was placed close tothe flat tube at the bottom. During a frosting experiment, there was no obvious attenuation of the heating performance of the two heat exchangers of different structures under the conditions of -7/-8 ℃ and 7/6 ℃. In addition, the evaporator/condenser with a horizontal structure had an obvious advantage during frosting and defrosting under a condition of 2/1 ℃.